A New Deal for Navajo Weaving : Reform and Revival of Diné Textiles - McLerran, Jennifer (Book collections on Project MUSE., 2022)
"A New Deal for Navajo Weaving provides a history of early to mid-twentieth-century Dine weaving projects by non-Natives who sought to improve the quality and marketability of Dine weaving but in so doing failed to understand the cultural significance of weaving and its role in the lives of Dine women"--